Performance analysis of UAV-assisted coverage for cell edge - Huakui Sun; Yang Zhou (PLoS ONE, 2026)
Unmanned aerial vehicles (UAVs), with their rapid and flexible deployment capabilities, have emerged as an effective solution for providing emergency wireless connectivity in scenarios where traditional ground base stations (GBSs) cannot offer reliable communication links. To address the weak coverage experienced by cell-edge users associated with a GBS, this paper investigates a UAV-assisted surround-enhancement coverage strategy. In the proposed approach, the original cell is partitioned into two service regions, where the GBS and UAV individually support users within their designated coverage areas. To improve spectrum utilization efficiency, we analyze the mutual interference between the UAV and GBS under a spectrum-sharing framework. Meanwhile, the user distribution within the cell is modeled as a homogeneous Poisson point process, and both the GBS and UAV randomly allocate channels to their associated users. Analytical results demonstrate that the UAV-assisted scheme exhibits an optimal surround radius and flight altitude, and that a reasonable division of coverage regions between the GBS and UAV can fully leverage their respective coverage capabilities.